PREVALENCE OF BOVINE SALMONELLOSIS IN ORGANIZED DAIRY FARMS - Upadhaya, Ankur; Swamy, Madhu; Dubey, Amita; Srivastav, Dharam Prakash (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Serum samples were collected from 101 animals from organized dairy farms of Jabalpur district. Slide micro agglutination test was employed to assess the sero-prevalence of Salmonella agglutinins in calves as well as adult bovine. Samples were collected from both diarrhoeic and non diarrhoeic apparently healthy animals. The sero-agglutination was observed in 14.5 per cent diarrhoeic cases. Maximal seroprevalence was detected in diarrhoeic adult buffalo (50%). Agglutination was observed in 22.6 per cent non diarrhoeic apparently healthy animals comprising 06, 02, 03 and 01 cases from cattle calf, buffalo calf, adult cattle and adult buffalo, respectively.